Design and fabrication of pestle and mortar machine / Muhammad Izzat Lukman - Lukman, Muhammad Izzat (2023)
This report presents information about the design and fabrication of pestle and mortar machines. A pestle and mortar are a set of two simple tools used to prepare ingredients or substances by crushing and grinding them into a fine paste or powder in the kitchen, laboratory, and pharmacy. The main problem with the pestle and mortar nowadays is that it is still used manually or by hand. This method uses a lot of human labour and takes a lot of time. The objective of this project is to develop a machine that can move a pestle and mortar automatically. This machine will use mechanical mechanisms, electric circuits, and other electric components to function. Hopefully, after this project is finished, it can help humans by converting human energy into electrical energy.